Financial Literacy Improvement Through Family Financial Planning Management Training - Stannia Cahaya Suci; Cep Jandi Anwar; Vadilla Mutia Zahara; Rah Adi Fahmi Ginanjar (EQUATOR SINAR AKADEMIA, 2022)
Financial inclusion has become one of the world's concerns, but Indonesia's level of financial inclusion is still quite low. The financial literacy index of Banten Province is low at only 38.18% in 2016 (OJK 2016). Desa Pasuluhan is one of the villages in Serang, Banten Province which has high economic potentials but in general, the people do not understand how to manage finances well. Therefore, Kegiatan Pengabdian Masyarakat is carried out to increase the knowledge and ability of the community for short-term and long-term financial goals planning. The method used is training and presentation. The results of this activity received a response of satisfaction from the participants as well as a greater understanding of the ability of participants in planning family financial management. In the long term, family management planning training activities in Desa Pasuluhan are expected to increase the level of financial inclusion at both the provincial and national levels.